Niccolò paganini: Medical and historical analysis of a great artist (2018)
Paganini's name is a clear historical trademark of outstanding musical performance and a very distinct example of the mysteries of the occult surrounding the lives of exceptional musicians. We have delved into the medical aspects and the myth created around the violinist's life in order to shed light on the legend of this wondrous artist. © 2018 Asociation Argentina de Dermatologia. All rights reserved.